Effect of Incivility, Resilience, and Social Support Experienced by Nursing Students on Burnout in Clinical Practice - Eun Jung Lee; Mi Hae Sung; Hye Kyong Ahn; Yun Ah Kim (Korean Society of Women Health Nursing, 2019)
PURPOSE: The purpose of the study was to determine effect of incivility, resilience, and social support experienced by nursing students on burnout in clinical practice. METHODS: Subjects were 140 nursing students who agreed to participate in this study. Collected data were analyzed using descriptive statistics, t-test, analysis of variance, Pearson's correlation and stepwise multiple regression with SPSS WIN 23.0 program. RESULTS: Burnout showed significantly positive correlation with incivility but significantly negative correlations with resilience and social support. Factors affecting burnout were satisfaction with major-dissatisfaction, satisfaction with major-average, social support, grade, and relationship with peers. Satisfaction with major (dissatisfaction) had the greatest effect on burnout, explaining 41% of the total variance. CONCLUSION: According to this study, dissatisfaction with major was identified as the most significant factor influencing burnout of nursing students in clinical practice. Therefore, it is important to develop and implement programs that can reduce dissatisfaction with major and increase social support and relationship with peers in order to lower burnout of nursing students. In addition, a systemic management of fourth-grade students with a high level of clinical practice is necessary to reduce the level of clinical practice. The authors declared no conflict of interest.